Modelling the seasonally dry tropical forests in the Semiarid region of Brazil: current and future distribution in CMIP-5 scenarios - Oliveira, Guilherme de Castro (2020)
Climate models of the Intergovernmental Panel on Climate Change, 5th Assessment Report (IPCC AR-5) predict scenarios of increasing aridity in the semiarid region of Brazil throughout the 21st century. The expansion of the dry zone has a high potential for environmental and socio-economic impact 1n the region and may affect biodiversity, ecosystem services and agricultural systems severely. As a result, the impacts of environmental changes may lead to mass migration 1f they make these regions uninhabitable. To develop consistent conservation and adaptation strategies for impacts mitigation, 1t Is necessary to employ multiple tools to estimate the potential effects of environmental changes in ecosystems. One of these tools 1s the environmental niche modelling, whereby the current distribution of species and plant formations 1s compared to the potential distribution in climate scenarios. However, for the semiarid region of Brazil, no studies have assessed these potential impacts 1n detail, to date. To enable this, 1t is necessary to deepen the knowledge of the environment-vegetation relationship in the Seasonally Dry Tropical Forests that occur in the region. In this context, the central objectives of this thesis were: a) to differentiate the main vegetations found in the semiarid region, stressing the distinction between the Arboreal Caatinga and the Atlantic Dry Forest in the southem semiarid ecotone and, b) to evaluate the climate change impacts on vegetation distribution 1n the RCP 4.5 and RCP 8.5 scenarios. Itis concluded that climate change will lead to the expansion of the Caatinga biome, particularly southward (North of Minas) and to the west of Bahia. However, the General Circulation Models were conflicting, resulting in high uncertainty mn the prediction models. This uncertainty was significantly reduced with the inclusion of soil attributes, which led to more consistent outputs. Soil attributes were also crucial to distinguish vegetations 1n the current climate at the regional and local scales. The physiognomic-based criteria to distinguish Atlantic Dry Forest and Arboreal Caatinga in the southern semiarid ecotone was Inaccurate to represent the species pool. Conversely, climate and soil explamed most of the variation 1n species composition. The lower dissimilarity among Arboreal Caatinga communities suggests that this vegetation was changed by abiotic homogenization. Niche models can improve the phytogeographic classification and provide more accurate assessments of the environmental changes impacts 1n the semiarid region. Keywords: Climate change. Caatinga. Niche Modelling. Dry tropical forests.